MODERN VIEWS ON THE CIRCULATION OF HERPES VIRUSES IN THE OKHOTSK SEA STELLER SEA LION (EUMETOPIAS JUBATUS, SCHREBER, 1776) - A. A. Derko; A. Yu. Alekseev; K. A. Sharshov; V. N. Burkanov; J. M. Jamalutdinov; G. N. Abdulgalimova; P. M. Ibnumaskhudova (Юг России: экология, развитие)
Aim. To evaluate the possibility of herpes viruses circulation and possible routes of transmission in population of Steller sea lions of the Sea of Okhotsk by combining a thorough literature study with screening of blood sera samples of Steller sea lion puppies of the Sea of Okhotsk obtained in 2008‐2012.Methods. We investigated 370 blood sera of puppies of the Steller sea lion (2008‐2012) from Tyulenij island, Chkalova island and from the Kurile Islands for the presence of antibodies to two members of the subfamily Alphaherpesvirinae and Gam‐ maherpesvirinae using enzyme‐linked immunosorbent assay (ELISA).Results. The data showed that out of 370 sera samples, 50 contained antibodies to the varicella‐zoster virus (subfamily Alphaherpesvirinae) and 46 – to the Epstein‐Barr virus (subfamily Gammaherpesvirinae).Main conclusions. The literature study revealed that the ecology peculiarities of species contribute to the realization of the main ways of transmission of herpes viruses between individuals. We were also able to identify possible risk factors for the transmission of non‐specific herpes viruses between Steller sea lion and the animals with which they are forced to coexist. The results obtained are in a good agreement with the literature data and indirectly confirm the circulation of herpes viruses in the Steller sea lion of the Kuril Islands, as well as the island Tyulenij. We observe a significant difference in the number of Steller sea lion puppies with the presence of antibodies to gamma‐herpes viruses on the Kuril Islands and the Okhotsk Sea is‐ lands (Р > 99,7). Differences in the number of Steller sea lion puppies with the presence of anti‐ bodies to alpha herpes viruses were not reliably detected.